Meta-Analysis of the Diagnostic Value of Cell-free DNA for Renal Cancer - Xu, Yipeng; Jiang, Yingjun; Yu, Mingke; Lou, Jianmin; Song, Mei; Xu, Han; Cui, Yingying; Zeng, Xiaowei; Wang, Qibo; Ma, Hanyun; Wang, Zongping; Zhu, Shaoxing; et al. (Frontiers in Molecular Biosciences, 2021)
Cell-free DNA (cf-DNA) has been reported to represent a suitable material for liquid biopsy in the diagnosis and prognosis of various cancers. We performed a meta-analysis of published data to investigate the diagnostic value of cf-DNA for renal cancer (RCa). Systematic searches were conducted using Pubmed, Embase databases, Web of Science, Medline and Cochrane Library to identify relevant publications until the 31st March 2021. For all patients, we evaluated the true diagnostic value of cf-DNA by calculating the number of true positive, false positive, true negative, and false negative, diagnoses by extracting specificity and sensitivity data from the selected literature. In total, 8 studies, featuring 754 RCa patients, and 355 healthy controls, met our inclusion criteria. The overall diagnostic sensitivity and specificity for cf-DNA was 0.71 (95% confidence interval (CI), 0.55-0.83) and 0.79 (95% CI, 0.66-0.88), respectively. The pooled positive likelihood ratio and pooled negative likelihood ratio were 3.42 (95% CI, 2.04-5.72) and 0.36 (95% CI, 0.23-0.58), respectively. The area under the summary receiver operating characteristic curve was 0.82 (95% CI, 0.79-0.85), and the diagnostic odds ratio was 7.80 (95% CI, 4.40-13.85). Collectively, our data demonstrate that cf-DNA has high specificity and sensitivity for diagnosing RCa. Therefore, cf-DNA is a useful biomarker for the diagnosis of RCa.